Views of Bumi Siliwangi Dormitory Residents on the Need for the Use of Rainwater Reservoirs - Nursyifa, Meta; Sundari, Hani; Nazwah, Nazwah; Trisetiyani, Syifa Dinda; Ramadani, Monica Safitri (Riviera Publishing, 2024)
The Bumi Siliwangi Dormitory is a facility provided by the University of Education Indonesia with a total of three buildings, including the women's dormitory building, the men's dormitory building, and the men's and women's runaway building. This study aims to examine the perception of dormitory residents towards the urgency of using rainwater reservoirs in the Bumi Siliwangi Dormitory, Universitas Pendidikan Indonesia (UPI), as well as to find out the number of clean water needs of dormitory residents, as an effort to overcome the problem of lack of clean water due to water pumps that are often damaged. This research method uses a descriptive method with a quantitative and qualitative approach. Primary and secondary data were collected from the Bumi Siliwangi Dormitory Building, with the research subjects in the form of dormitory residents and dormitory managers. The analysis of water needs is carried out based on urban water demand standards. The results of the study show that the dormitory water requirement is 18,352,200 liters/year, while the clean water capacity produced reaches 78,840,000 liters/year. Based on these results, it can be concluded that rainwater harvesting is not needed at this time.